Infective Endocarditis - Diagnosis, Treatment and Specific Situations Management – Current Knowledge, Review of the Literature - Balwierz, Magdalena; Kosińska, Agnieszka; Belcarz, Wiktoria (Quality in Sport, 2025)
Introduction Infective endocarditis (IE) is a severe condition of endocardium, which can manifest through a wide spectrum of unspecific symptoms related to various organ systems. The diagnosis is made on the basis of the presence of bacteraemia and imaging findings confirming IE visualized in echocardiography, computer tomography and nuclear imaging. Anatomical changes or foci of altered metabolism can be located on the valves, in the perivalvular area or in the area of foreign material (e. g. valves prosthesis or implantable device). Not only the diagnostic process can be challenging, but also the treatment, which consists of antibiotic therapy and cardiac surgery. The indications for surgical treatment depend on patients’ clinical condition, which can change dynamically. Multidisciplinary approach is required to the proper care of the patients. Aim of the study The aim of the study is to review the current knowledge of infective endocarditis and the timing indications of cardiac surgery treatment. Material and methods This article presents the current knowledge of the diagnosis and treatment in infective endocarditis, especially on the basis of the guidelines of European Society of Cardiology. Literature analysis, especially papers, which contain recent report in infective endocarditis treatment were analysed using the PubMed platform. The search included the keywords: “infective endocarditis”, ,‚surgery treatment of infective endocarditis”, “endocarditis team”, “CIED- related infective endocarditis”.